Motives of the Soldiers of Kaunas Self-Defence Battalions for Participation in the Killing of Jews and Other Groups of People during the Nazi Occupation (1941–1944) - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2011)
The article explores the motives of Lithuanians, who served in Kaunas National Labour Defence 1st and 2nd Auxiliary Police Service Battalions, for killing Jews and other groups of people during the period of the Nazi occupation (1941−1944). The topic is examined on the basis of archival data, historiography, and the knowledge of social psychology. The article distinguishes six inner factors that encouraged the troops who served in Kaunas National Labour Defence Battalions to participate in the massacre campaigns. They are: duty, fear, negative images, sadism, inebriation, and the need for property. The main factor, however, that urged the troops to participate in the massacre was the sense of duty. This was the main factor, because soldiers who joined the battalion had undertaken to obey orders. The operations of the extermination of Jews and other groups of people were carried out pursuant to the orders issued to them, i.e. first there was an appeal to the sense of duty and only then to other internal factors. There were five internal factors considered to be internal stimuli that encouraged the fulfilment of duty. The feeling of duty and the motive of fear were characteristic to all soldiers involved in the campaigns of killing people. Negative images, sadism, inebriation, and the need for property were characteristic of only some soldiers of the battalions. The article also discusses the cases in which soldiers of Kaunas Self-Defence Units carried out actions directed against Jews outside the battalion or prior to joining the battalion. Such acts were carried out due to negative images, which evoked feelings of hatred and revenge. These actions are special because when carrying out of these actions, soldiers were not bound by a sense of duty, i. e. the sense of duty did not determine their actions. In this case, therefore, negative images should be considered the key factor that encouraged the act of killing.